Immune responses during an antarctic summer - Lugg, Desmond J.; Ursin, Holger; Donovan, Kevin; Konrad Muller, H.; Quinn, Dennis (Pathology, 1995)
The immune status of 29 members of the Australian National Antarctic Research Expeditions (ANARE) was investigated before, during, and after a 56 day summer voyage to Antarctica and correlated with psychological and physiological parameters. All subjects were healthy. Expedition personnel demonstrated decreased cell mediated immune responses (CMI) assessed by the CMI Multi-test; 21% were hypoergic. The major associated observation was a significant negative correlation with anxiety in Antarctica. However, perceived anxiety was greater before and after the voyage. No significant changes were found in T and B lymphocyte subsets, immunoglobulin and complement components and cutaneous blood flow, nor was there any clinical evidence of illness. Of the hormones examined only cortisol was low predeparture which may reflect increased perceived anxiety at that time. Changes in immune control mechanism were apparent as shown by reduced CMI responses and lowered tetanus antibody levels. Stress factors are postulated to induce depression of the immune response in Antarctica. The association with anxiety suggests that brain peptides or associated cytokines may have a role in mediating these immune events. Such alterations in immune status have implications for health management in isolated and extreme conditions.
Keywords: Antarktis; fysiologi; immunologi; psykologi

Light and productivity of phytoplankton in polar marine ecosystems: a physiological view - Sakshaug, Egil; Slagstad, Dag (Polar Research, 1991)
Keywords: Sørishavet; fysiologi; fytoplankton; planteplankton; polarområdene

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues - Ursin, Holger; Bergan, Tom; Collet, Jérôme; Endresen, Inger M.; Lugg, Desmond; Maki, Pauline; Matre, Roald; Molvær, Otto Inge; Müller, Helmut K.; Olff, Miranda; Pettersen, Roger C.; Sandal, Gro Mjeldheim; et al. (Environment and Behavior, 1991)
Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.
Keywords: Antarktis; forskningsstasjoner; fysiologi; immunologi; psykobiologi; psykologi